Manipulate an air–cathode fuel cell toward recovering highly active heterogeneous electro-Fenton catalyst from the Fe(II) in acid mine drainage. (December 2015) - Sun, Min; Wu, Ning-Ning; Zhai, Lin-Feng; Ru, Xiao-Rui
Highlights: Fabricate Fe3 O4 /GF composite as electro-Fenton catalyst from acid mine drainage. Manipulate air–cathode fuel cell to precipitate iron oxides on GF. Activity of Fe3 O4 /GF depends upon iron loading and Fe3 O4 morphology in composite. Solution pH and composition in fuel cell affect electro-oxidation of Fe(II). Distribution of Fe(II) species in fuel cell controls structure of Fe3 O4 /GF. Abstract: The recovery of iron oxides from acid mine drainage (AMD) has attracted extensive research attention due to the double advantage of waste minimization and resource recovery. Recently a novel air–cathode fuel cell approach was proposed to in-situ utilize ferrous iron (Fe(II)) in the AMD for the fabrication of Fe3 O4 /graphite felt (GF) composite as the cathode of electro-Fenton process. In the present work, the influence of fuel cell operating parameters, including solution pH, carbonate concentration and Fe(II) concentration, on the catalytic activity of prepared Fe3 O4 /GF composite is adequately elucidated. The highest activity is observed on the composite obtained from the fuel cell operated with 30 mM Fe(II) and 50 mM carbonate at pH 7.5. The activity of Fe3 O4 /GF is strongly dependent upon iron loading and Fe3 O4 morphology in the composite. Higher iron loading generally induces higher catalytic activity, and the Fe3 O4 aggregate is catalytically less reactive relative to the well-dispersed one. The precipitation of Fe(III) oxides on the GF through electrochemical oxidation of Fe(II) plays a key role in determining the structure of Fe3 O4 /GF composite. Solution pH and composition in the fuel cell affect such a process by manipulating the distribution of Fe(II) species in aqueous solution and on the GF.